1999
DOI: 10.3133/ofr99462
|View full text |Cite
|
Sign up to set email alerts
|

Construction and calibration of numerical ground-water-flow models of the western half of the Milford-Souhegan glacial-drift aquifer, Milford, New Hampshire

Abstract: The Milford-Souhegan glacial-drift (MSGD) aquifer, in southcentral New Hampshire, is an important source of water for industrial, commercial, and domestic use that provides more than 2.7 million gallons of water per day in 1994. A large plume of volatile-organic compounds (approximately 0.5 square miles in area) covers a large part of the western half of the MSGD aquifer and threatens existing groundwater usage. The plume area has been designated a superfund site and named after a former municipal water-supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Seasonal trends in direct infiltration recharge from precipitation and recharge from river leakage cause directional variations in flow that affect capture of the contaminated ground water by the existing exterior extraction wells as shown by numerical simulations of transient hydrologic conditions. Monitoring data indicate that maximum gradients and recharge from the losing river reach in OU1 are generally during low water-table conditions (Harte, 1999). Therefore, if exterior extraction at EW-1 and EW-2 is turned off during low recharge periods (summer), then less, relatively clean ground water from the river area is captured.…”
Section: Evaluation Of Effectiveness Of Remediationmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal trends in direct infiltration recharge from precipitation and recharge from river leakage cause directional variations in flow that affect capture of the contaminated ground water by the existing exterior extraction wells as shown by numerical simulations of transient hydrologic conditions. Monitoring data indicate that maximum gradients and recharge from the losing river reach in OU1 are generally during low water-table conditions (Harte, 1999). Therefore, if exterior extraction at EW-1 and EW-2 is turned off during low recharge periods (summer), then less, relatively clean ground water from the river area is captured.…”
Section: Evaluation Of Effectiveness Of Remediationmentioning
confidence: 99%
“…The amount of aquifer recharge from the losing river reach in OU1 affects ground-water-flow direction outside the barrier. Harte (1999) showed that maximum gradients occur during low water-table conditions in the aquifer because aquifer recharge from the river reach in OU1 is highest during this period. When recharge is highest from the river, more flow occurs from the river area toward EW-1 and EW-2.…”
Section: Simulation Of the Remedial System And Its Operationmentioning
confidence: 99%